Diagnóstico de salud bucodental y factores de riesgo en el Centro Educativo Primario Alvarez Sánchez Colombia de la Parroquia Rural Gualel del cantón Loja año 2013 - Condolo Torres, Jenny Patricia (2013)
The importance of the buccal health resides in the prevention of different illnesses that you/they are harmful for our physical and emotional well-being, A good hygiene begins with a correct brushing that should be carried out after each food, ingesta of drinks, especially the sugary and carbonated, of goodies or appetizers, or of any food. The objectives of the present work were to diagnose the present pathologies, the factors of risk, and the prevalencia of this pathologies in the students the School of Basic Education "Álvarez Sánchez Colombia" of the rural parish Gualel of the canton Loja, one worked with 295 students, and for the obtaining of the data a survey, the same one was used that was filled in way written by the students and a history clinical odontológica where he/she registered the obtained results the same ones they were: decay dental in 93,2%, inflammation gingival and bled 12,5%, the relationship molar in the temporary teething was right plane terminal in 67,7%, in permanent teething it was class I with packing in 55,4%, the factors of risk were brushed incorrect 88,8%; it visits once to the odontologist a year 69.8%, consumption of foods cariogénicos of three times a day with a 61,%. After having carried out the study you can conclude that a high index of alterations of the buccal cavity exists, the same ones that influence negatively in the state of the population's general health, and that affects without a doubt some to the development characteristic of the person and of the community on the whole. For what is recommended promotion campaigns and oral prevention, to the population of more risk. Key Words: Decay, inflammation gingival, bad occlusion and factors of risk.